Sinais que conferem credibilidade a Moisés: um estudo exegético de Êxodo 4,1-9 - Fobe, Jean Luc (2020)
The pericope from Exodus 4,1-9 is part of the historical and epic narrative of the liberation of the hebrew people from the oppression of Egypt. This micronarrative is the third of Moses' challenges to his mission as a liberator commissioned in the greater context of Exodus 3,1-4,17. Moses' excuse, as a reluctant hero, is that he would not be recognized as commissioned by YHWH, and who would not have made himself visible. YHWH's answer is given with two signs and one more, confirming that Moses would have credibility as a commissioned messenger, with power and authority. The micronarrative was submitted to morphosyntactic and literary analysis, with identification of the symbology of the three signs described and the theological message. The first sign of throwing the staff to the ground, which is transformed into a serpent and its further restoration. This sign was interpreted as the divine judgment on Egypt, and the divine power commissioned over the absolute evil represented by Apep. The second sign of the transformation of Moses' hand into leper compared with the snow, and subsequent restoration, was related with the sanctity of his actions. Biblical leprosy has three distinct attributive descriptions: like snow, flaking and whitish that affected Moses and Miriam, in Ex 4,6 and Nm 12,10; uncharacteristic skin disease that affects people, in Lev 13-14; and the plague on the walls at Lv 14,34. Leper compared with the snow has been identified as plaque psoriasis. The third sign with the transformation of water into blood represents the power of YHWH against the Nile, with the libertarian confrontation between the blood of the oppressed and the exploitation of natural wealth by the oppressor in Ex 2,11.13-14, which is completed in ten plagues in Ex 7.17-2. The first two supernatural signs that YHWH makes through the hands of Moses on mount Horeb, and the third, foreshadowed on the Nile, gives credibility, transfer divine power, authority, confirm his commissioning as liberator and messenger, and his insertion in the chronological history of Israel, compared to the ancient patriarchs